Comparing Protection of Remote Limb with Resveratrol Preconditioning following Rodent Subarachnoid Hemorrhage - Sebastian Koch; Giselle De La Rua; Donnae Farquharson; Isabel Saul; Miguel Perez-Pinzon; Kunjan Dave (Biomolecules, 2022)
Background: Preventing delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH) remains an important therapeutic target. Preconditioning stimulates multiple endogenous protective mechanisms and may be a suitable treatment for DCI following SAH. We here compare remote limb conditioning with resveratrol conditioning in a clinically relevant SAH model. Methods: We produced a SAH in 39 male Sprague Dawley rats using a single injection model. Animals were randomized to four groups: repetitive limb conditioning with a blood pressure cuff, sham conditioning, intraperitoneal resveratrol (10 mg/kg) or intraperitoneal vehicle administered at 24, 48 and 72 h after SAH. On day 4 neurological and behavioral scores were obtained, and animals were euthanized. The cross-sectional area of the basilar artery was measured at the vertebrobasilar junction, and at the mid and distal segments. Hippocampal cells were counted in both hemispheres and normalized per mm length. We compared true limb preconditioning with sham conditioning and resveratrol with vehicle preconditioning. Results: The cross-sectional area of the mid-basilar artery in the true limb preconditioning group was significantly larger by 43% (p = 0.03) when compared with the sham preconditioning group. No differences in the cross-sectional area were found in the resveratrol-treated group when compared to the vehicle-treated group. We found no differences in the neuro score, behavioral score, and in mean hippocampal neuron counts between the groups. Conclusion: We found beneficial vascular effects of remote limb preconditioning on SAH-induced basilar artery vasoconstriction. Our findings support further studies of limb preconditioning as a potential treatment after SAH.